Model Praktik Lembaga Keuangan Mikro Syariah dalam Pemberdayaan UMKM di Masa Pandemi Covid-19 - Herawati, Herawati; Sahrani (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2024)
Micro and small enterprises (UMKM) are key actors in the economy. These business entities play a crucial role in national economic development, such as contributing to the gross domestic product, creating jobs, and making investments. This study aims to analyze the operational models of research institutions. LKMS (Islamic Microfinance Institutions) empower SMEs in Indonesia. The analysis describes these models. The findings explain the impact of microfinance on strengthening small enterprises. From a modeling perspective, LKMS can enhance the production of small and medium enterprises. There are various microfinance models to strengthen small businesses. Specifically, Islamic financial institutions can utilize these models, which include solidarity groups, village bank models, grammar models, and individual models